Analysis of antioxidant and antibacterial activity of cocoa pod husk extract (Theobroma cacao L.) - Rahayu, Yani Corvianindya; Setiawatie, Ernie Maduratna; Rahayu, Retno Pudji; Ramadan, Doaa Elsayed (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Theobroma cacao bean manufacturing worldwide includes undesired byproducts such as cocoa pod husks. Cocoa pods contain a variety of beneficial chemicals, including polyphenols. Polyphenols have a vital function in the treatment of many illnesses and infections of the oral cavity. This is due to their vital qualities in the oral cavity, including anti-inflammatory, antibacterial, and antioxidant actions. Purpose: The goal of this study was to look at the antioxidant content and antibacterial activity of cocoa pod husk extract (Theobroma cacao L.) against Phorphyromonas gingivalis (P. gingivalis) and Streptococcus mutans (S. mutans). Methods: Cocoa pod husk extract was produced using an ultrasonic homogenizer and 70% ethanol. Thin layer chromatography and the Folin–Ciocalteu test were used to determine the phytochemical content and total phenolic content of the extract. The 2,2-diphenyl-1-picryl-hydrazyl-hydrate technique was used to measure antioxidant activity. Minimum inhibitory concentration (MIC) tests were used to measure the antibacterial activity of ethanolic extract at concentrations of 1, 4, 8, 16, 32, and 64 mg/ml using a deep-well broth microdilution technique. Results: The presence of alkaloids, flavonoids, tannins, saponins, and triterpenoids was discovered in the cocoa pod husk extract. Conclusion: The antioxidant activity of the extract was significant (IC50 = 62 ppm), and the MIC of P. gingivalis and S. mutans was 16 mg/ml and 8 mg/ml, respectively.